2009
DOI: 10.1111/j.1447-0756.2008.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of markers for fetal inflammatory response syndrome: Fetal blood interleukin‐6 and neonatal urinary β2‐microglobulin

Abstract: We suggest that measuring urinary beta(2)-MG in premature infants soon after birth can monitor FIRS and may provide information on the risk of subsequent CLD development that is as clinically important as information derived from umbilical cord blood IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
(19 reference statements)
0
24
0
Order By: Relevance
“…It is worthwhile to note, however, that even with no observable cytokine migration during late gestation, maternal infection during this period still results in an increase in cytokine levels in the fetal CNS as there have been observations of increased cytokine mRNA and protein levels, as well as other immunological disruptions in FIRS infants [54,59,78,154] . Additionally, observations in models of MIA mimic FIRS findings of increased inflammatory cytokines and other immunological events in the fetal CNS in response to maternal injection, including the induction of monocyte chemoattractant protein-1 and increased glial cell reactivity [156,157] .…”
Section: Mia and The Placental Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to note, however, that even with no observable cytokine migration during late gestation, maternal infection during this period still results in an increase in cytokine levels in the fetal CNS as there have been observations of increased cytokine mRNA and protein levels, as well as other immunological disruptions in FIRS infants [54,59,78,154] . Additionally, observations in models of MIA mimic FIRS findings of increased inflammatory cytokines and other immunological events in the fetal CNS in response to maternal injection, including the induction of monocyte chemoattractant protein-1 and increased glial cell reactivity [156,157] .…”
Section: Mia and The Placental Barriermentioning
confidence: 99%
“…Despite these studies, there is still disagreement as to whether or not these maternal cytokines, produced during maternal infection, can traverse the placental barrier and disrupt normal fetal development. Research in FIRS has shown that in instances of maternal infection, the placenta can become inflamed, producing cytokines such as IL-6 which is a key biological marker in FIRS often detected in the amniotic fluid and maternal, fetal and umbilical cord serum [54,58,154,155] . Nevertheless, research focusing on the placental migration of cytokines, following maternal infection continues to yield contradictory results as some researchers have observed minimal cytokine migration while others note that the levels that cross the placenta are too negligible to exert any effect.…”
Section: Mia and The Placental Barriermentioning
confidence: 99%
“…Different authors have used different cut-off values of IL-6 for the diagnosis of EOS. Nishimaki et al 8 have used a cut-off of 54.7 pg/mL. Values as low as 10 pg/mL have been used by Martínez Nadal et al, 17 whereas Smulian et al 18 have used a cutoff of 25 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have documented high umbilical cord blood IL-6 concentrations in chorioamnionitis. [6][7][8] In the present study, we compared the statistical validity of cord blood IL-6 concentrations with conventional sepsis screening as an early diagnostic marker of EOS.…”
Section: Introductionmentioning
confidence: 99%
“…This result may be secondary to hypoxic stress that caused subclinical tubular dysfunction [30]. Nishimaki and Shima et al, [31] reported that increased urinary β2MG at birth can indicate fetal inflammatory response and may provide information on the risk of subsequent chronic lung disease.…”
Section: Discussionmentioning
confidence: 99%